Effect of acid concentration on organic structure and small molecule stripping of coal during acid treatment and electrolysis for hydrogen production. (15th August 2023) - Chen, Cong; Liu, Jianzhong; Wang, Jianbin; Li, Dedi; Chen, Yitong; Cheng, Jun
Highlights: The effect of the electrolyte itself on the coal particles cannot be ignored. Judging the reactivity of coal only from the current density will produce errors. Most of the liquid phase organics are oxygenated, and oxidative shedding dominates. Abstract: Coal-assisted water electrolysis for hydrogen production can effectively reduce electricity consumption and improve the economics of electrolytic hydrogen production technology. However, the influencing factors of this process, especially the mechanism of the electrolyte itself on the coal particles, are not clear. The influence of electrolyte on the electrooxidation process of coal particles is of great importance in practical applications. In this paper, detailed controlled experiments were designed to investigate the effect of electrolyte concentration on coal-assisted water electrolysis. And the laws of the acid leaching and electrooxidation processes on the macrostructure and organic structure of coal particles were investigated by various characterization methods. Information on the small molecules of organic matter stripped from coal molecules under different experimental conditions was also obtained by GC–MS. The results showed that the reactivity of coal particles decreased with increasing electrolyte concentration, and judging reactivity from current density alone would produce some errors. The rebound of current density in high concentration of sulfuric acid mainly came from more fragmentation of coal particles. The CO structure played a facilitating role in the oxidation of coal, while the CO and COOH structures would hinder the further oxidation of coal particles due to their stability. Small organic molecules were released from coal particles into the electrolyte during acid leaching and electrolysis, and the amount of small organic molecules detached was positively correlated with sulfuric acid concentration and oxidation charge, where oxidation detachment dominated.